Poczuć dźwięki. Wybrane metody terapii muzycznej w kontekście wad słuchu = To feel sounds. Choosen methods of music therapy in hearing defect context - Kataryńczuk-Mania, Lidia; Lis-Zaldivar, Anna (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
Authors talk about chosen auditory education issues, hearing lose and rehabilitation. They discuss chosen methods of work with people affected by hearing impairement in area of Mobile Music Recreation, according to Maciej Kierył, Massage by sound according Emil J. Dalcroze, in conception of Carl Orff and music program MAKATON.
Keywords: dźwięk; muzykoterapia; terapia słuchowa; sound; music therapy; auditory therapy